3D driven hard tissue augmentation based on reverse planning Reconstruction of an advanced, horizonto-vertical alveolar ridge defect: A case report. (June 2022) - Bolya-Orosz, Fanni; Palkovics, Daniel; Gergely, Zsófia; Windisch, Peter
Abstract : Purpose: This case report presents a novel, 3D-driven reverse planning for surgical rehabilitation of an advanced alveolar ridge defect. Utilizing a completely digital workflow, alveolar ridge augmentation could virtually be simulated thus simplifying the surgical procedure. Methods: In this case report the digitally planned treatment of a severe horizontovertical alveolar ridge defect is presented. Preoperative cone-beam computed tomography (CBCT) scan was segmented using a semi-automatic segmentation technique in an open-source medical image processing software (3D Slicer) to develop virtual 3D models of dental and alveolar structures. Intraoral scan, bite registration was also acquired to generate a digital wax-up. Consequently, prosthetically ideal implant positions could be planned in 3D. Based on future implant positions, adequate amount of hard tissue augmentation could be planned virtually. Individualized form of the barrier membrane could be determined, allowing the additive manufacturing of a membrane cutting template for shaping the barrier membrane during surgery. The combination of a non-resorbable barrier membrane, tenting screws, and composite graft (50% xenograft, 50% autogenous bone) was utilized. A follow-up CBCT scan was taken after 9 months to determine volumetric and 3D morphological changes. Results: After 9 months, a hard tissue gain of 0.81 cm 3 could be observed. During the 6-9 month healing period membrane exposition did not occur. Conclusions: Virtual planning and subsequent surgical simulation on 3D models is a novel method in "prosthetically driven" augmentation potentially reducing the duration of surgery and postoperative complications. However, further studies are necessary to drive any more conclusions.